Analisi di costo efficacia nella terapia della BPCO - Iannazzo, Sergio; Pradelli, Lorenzo; Negro, Roberto W. Dal; Eandi, Mario (Farmeconomia. Health economics and therapeutic pathways, 2005)
Current practice guidelines for the treatment of COPD recommend the use of combined inhaled corticosteroids and long-acting bronchodilators in severe and very severe patients (GOLD stages III and IV). OBJECTIVES: To analyze the economical and clinical impact of this recommendation, the affordability of its widespread application, as well as the relative pharmacoeconomical performance of the available options for severe and very severe COPD in Italy. METHODS: Published data on the Italian COPD population were fitted in a disease progression model based on a Markov chain representing severity stages and death. Alternative therapeutic options (salmeterol/ fluticasone - SF, formoterol/budesonide - FB, salmeterol alone - S, fluticasone alone - F and control - C) were represented as competing arms in a decision tree. Efficacy data from international trials were expressed in terms of risk reduction. Clinical parameters used were number of exacerbations and symptom-free days. Direct and indirect costs were considered and valued according to present prices and tarifs. The analyses were conducted from National Health System, societal and patient perspectives with time horizons of 1,5, and 10 years, and lifelong. RESULTS: The yearly total direct costs of treating COPD patients in Italy is estimated in approximately 7 billion Euro, with a mean cost/patient/year around 2,400 Euro. Mean survival of the cohort is 11,5 years. The C and F strategies are dominated (i.e. are associated with worse outcomes and higher costs) by all alternatives. S/F and F/B are the most effective strategies, with a slight clinical superiority of the latter, but are also marginally more expensive than S. Incremental cost/effectiveness of S/F vs. S is 679,55 Euro/avoided exacerbation and 3,31Euro/gained symptom-free day. CONCLUSIONS: The recommended use of combined inhaled corticosteroids and long-acting bronchodilators for severe and very severe COPD patients, as compared with current practice, has the potential of improving clinical outcomes without increasing health care costs.